LETHAL CONCENTRATION 50% OF PATCHOULI OIL (Pogostemon cablin) TOWARDS ZEBRAFISH EMBRYO (Danio rerio) - Romel Ciptoadi Wijaya (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
Preface :Patchouli Oil requires toxicity testing for safety before we can use it widely. It causes side effects such as nausea, vomiting and loss of appetite in some people. Determination of lethal concentration 50% (LC50) in the early stages of zebrafish embryos development will provide an easier, faster and precise prediction of toxicity. At a certain dose, it can cause impairment and death toward organisms. Therefore, the aim of this study was to determine LC50 of Patchouli Oil in carboximethyl cellulose emulsifier towards zebrafish embryo (Danio rerio).Method :Laboratory experimental study was using zebrafish embryos at 2 hours post fertilization. The total of 160 embryos were used and divided into 8 groups, i.e.; Negative control (KN) was given the embryonic fluid, positive control 1 was given 5000 ppm of patchouli oil (KP1), positive control was given 5000 ppm of CMC (KP2), and 5 treatment groups, i.e.; concentration of 10 ppm (P1), 30 ppm (P2), 60 ppm (P3), 90 ppm (P4) and 120 ppm (P5) of Patchouli oil which was emulsified in CMC. The study was conducted with 3 times repetition. Data collection was done by calculating total of embryo’s deaths for each treatment at 24-72 hours of exposure. Data were analyzed using Regression Probit Analysis.Results :Mortality in the group of KN was 1.6%, KP1 was 98.3% and KP2 was 0%. Meanwhile in the treatment group of P1, P2, P3, P4 and P5 respectively were 0%, 5%, 10%, 25%, and 50%.Conclusion :Based on these results, Lethal Concentration 50% of Patchouli Oil in CMC emulsifier towards zebrafish embryo is 120 ppm.